21st Century Character Education in Mathematics Learning for Elementary School Students - Rahayu, Desti; Narimo, Sabar; Fathoni, Achmad (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Character education has become an essential component of 21st-century learning, emphasizing not only cognitive achievement but also the development of students’ moral values, responsibility, collaboration, and critical thinking. Mathematics learning at the elementary school level provides opportunities to integrate these character values through problem-solving and cooperative learning activities. Objective: This study aims to describe the implementation of 21st-century character education in mathematics learning for elementary school students. Method: This study employed a descriptive qualitative research design. The research was conducted at SD Negeri 2 Sukorejo, Klaten, in 2022. The participants included the principal, teachers, and students. Data were collected through classroom observation, interviews, and documentation. The validity of the data was ensured through source triangulation, while the data analysis process involved data collection, reduction, data presentation, and conclusion drawing. Results: The findings indicate that 21st-century character education in mathematics learning is integrated into the Learning Implementation Plan (RPP) and classroom practices. Character values such as discipline, responsibility, cooperation, and critical thinking were embedded in learning activities and student interactions. Conclusion: Integrating character education into mathematics learning supports both academic understanding and character development among elementary students. Contribution: The study provides practical insights for teachers in implementing character-based mathematics learning in elementary schools.